Adsorbate enhancement of electron emission during the quenching of metastable CO at metal surfaces. Issue 17 (7th May 2015) - Engelhart, Daniel P.; Wagner, Roman J. V.; Johnsen, Peter C.; Wodtke, Alec M.; Schäfer, Tim
<x xml:space="preserve">Abstract</x> A monolayer of adsorbed rare gas dramatically enhances electron emission when quenching CO(a3Π) at metal surfaces.